Rebhun's diseases of dairy cattle. - Divers, Thomas J; Peek, Simon Francis; Rebhun, William C. (St. Louis : Saunders Elsevier, 2008)
With thorough coverage of differential diagnosis methods, surgical and therapeutic treatment options, and prevention strategies, this all-in-one guide provides the vital information you need to battle bovine diseases in both dairy and non-dairy cattle.--COVER
-- Pt. I. Examination and assessment. The clinical examination / Thomas J. Divers and Simon F. Peek -- Therapeutics and routine procedures / Thomas J. Divers and Simon F. Peek -- Pt. II. Diseases of body systems. Cardiovascular diseases / Simon F. Peek and Sheila M. McGuirk -- Respiratory diseases / Thomas J. Divers -- Noninfectious diseases of the gastrointestinal tract / Susan Fubini and Thomas J. Divers -- Infectious diseases of the gastrointestinal tract / David C. Van Metre, Bud C. Tennant, and Robert H. Whitlock -- Skin diseases / Danny W. Scott -- Diseases of the teats and udder / Lisle W. George ... [and others] -- Reproductive di seases / Robert Hillman and Robert O. Gilbert -- Urinary tract diseases / Thomas J. Divers -- Musculoskeletal disorders / Charles Guard -- Neurologic diseases / Alexander de Lahunta and Thomas J. Divers -- Ocular diseases / Ronald Riis -- Metabolic diseases / Simon F. Peek and Thomas J. Divers -- Miscellaneous infectious diseases / Franklyn Garry -- Miscellaneous toxicities and deficiencies / Franklyn Garry -- Append. 1. Important web links and phone numbers for dairy practitioners -- Legends for video clips / Amy e. Yeager ... [and others.
Rev. edition of: Diseases of dairy cattle/ by William C. Rebhun. 1995.
Includes bibliographical references and index.
Keywords: Cattle -- Diseases -- Diagnosis; Cattle -- Diseases -- Prevention; Cattle Diseases